An "in-out" strategy using gene targeting and FLP recombinase for the functional dissection of complex DNA regulatory elements: analysis of the beta-globin locus control region. - Fiering, S (1993)
The human beta-globin locus control region (LCR) is a complex DNA regulatory element that controls the expression of the cis-linked beta-like globin genes located in the 55 kilobases 3' of the LCR. We have initiated the functional analysis of the LCR by homologous recombination in murine erythroleukemia cell somatic hybrids that carry a single copy of human chromosome 11 on which the beta-globin locus is situated. High-level expression of the human beta-globin gene normally occurs when these hybrid cells are induced to differentiate. We have reported that the insertion of an expressed selectable marker gene (driven by the Friend virus enhancer/promoter) into the LCR disrupts the LCR-mediated regulation of globin transcription. In these cells, beta-globin is no longer expressed when the cells differentiate; instead, expression of the selectable marker gene increases significantly after differentiation. Since present techniques for homologous recombination require the insertion of a selectable marker, further progress in using homologous recombination to analyze the LCR depends on deletion of the selectable marker and demonstration that the locus functions normally after the insertion, expression, and deletion of the selectable marker. Here we show that after precise deletion of the selectable marker by using the FLP recombinase/FRT (FLP recombinase target) system, the locus functions as it did before the homologous recombination event. These studies demonstrate the feasibility of using homologous recombination to analyze the LCR in particular, and other complex cis-regulatory DNA elements in general, in their normal chromosomal context.